Role of health literacy on lifestyle and glycemic control among women with diabetes during pregnancy: a cross-sectional study - Babazadeh, Towhid; Pourrazavi, Sara; Ardeshiri, Zahra; Nadi, Akbar; Chollou, Khalil Maleki (Frontiers in Public Health, 2024)
Background: The present study aims to explore the impact of health literacy on the lifestyle of women with diabetes in pregnancy.A cross-sectional study assessed the influence of some demographic characteristic, heath literacy dimensions in predicting lifestyle and glycemic control in a sample of 230 women with diabetes in pregnancy. The data collection included a demographic form, Health Literacy scale and Life Style questionnaire. Data were analyzed using One-way ANOVA and Pearson's correlation coefficient. The predictors were also determined using hierarchical linear regression analysis.The participants had an average age of 27.74 years (SD= 6.54) and an average HbA1c level of 6.93% (SD= 1.93). About 51.0% of the variation in lifestyle can be explained by health literacy (HL) and demographic variables (p-value< 0.05). Additionally, approximately 15.0% of the variation in HbA1c can be explained by health literacy, lifestyle, and demographic variables (p-value< 0.05).Findings: According to our findings, decision-making was found to be the strongest predictor of lifestyle. This study provide valuable information for nurses and other health care providers to help empower pregnant women to increase health literacy and improve their lifestyle.